PENGEMBANGAN PEMBELAJARAN KEAGAMAAN DAN BAHASA ARAB DI MADRASAH IBTIDAIYAH MINORITAS MUSLIM - Ismail Suardi Wekke (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2017)
Arabic is the compulsory subject of elementary school in Ministry of Religious Affair, Indonesia. Therefore, it is a need to identify the Arabic teaching and learning in extending the new curriculum. This article discusses the development of Arabic teaching and learning in Muslim minority of West Papua. Qualitative approach was applied during research. It was started from focus group discussion to identify research problem among elementary school teacher. Observation and in-depth-interview were conducted to collect data. Three months serial observation and interview to students, teacher, and school management were employed in ensuring data collection was stimulated. This article shows that Arabic language teaching and learning in Muslim minority of West Papua was developed to articulate environmental need. In addition, there are circumstances during program acceleration. Therefore, there are programs to develop and extend classroom achievement. Finally, this article discusses initiatives from teachers and school management in expanding and enlarging learning opportunities not only in school area and time, but also outside school hours.